Insomnia diary - Hicok, Bob, 1960- (Pitt poetry series., 2004)
"The most potent ingredient in virtually every one of Bob Hicok's compact, well-turned poems is a laughter as old as humanity itself, a sweet waggery that suggests there's almost no problem that can't be solved by this poet's gentle humor."--New York Times Book Review